Body mass variability in age-matched outbred male Swiss mice is associated to differential control of food intake by ghrelin. (15th June 2022) - Morari, Joseane; Haddad-Tóvolli, Roberta; Silva Nogueira, Pedro Augusto; Teixeira, Caio Jordão; Maróstica, Rafael; Tobar, Natália; Ramos, Celso Dario; Velloso, Licio Augusto; Dias Bobbo, Vanessa Cristina; Anhê, Gabriel Forato
Abstract: Swiss mice belong to an outbred strain of mice largely used as a model for experimental obesity induced by high fat diet (HFD). We have previously demonstrated that a given cohort of age-matched Swiss mice is hallmarked by heterogeneous changes in body weight when exposed to HFD. The reasons underlying such variability, however, are not completely understood. Therefore we aimed to clarify the mechanisms underlying the variability in spontaneous weight gain in age-matched male swiss mice. To achieve that, individuals in a cohort of age-matched male Swiss mice were categorized as prone to body mass gain (PBMG) and resistant to body mass gain (RBMG). PBMG animals had higher caloric intake and body mass gain. RBMG and PBMG mice had a similar reduction in food intake when challenged with leptin but only RBMG exhibited a drop in ghrelin concentrations after refeeding. PBMG also showed increased midbrain levels of ghrelin receptor ( Ghsr) and Dopamine receptor d2 ( Drd2 ) mRNAs upon refeeding. Pharmacological blockade of GHSR with JMV3002 failed to reduce food intake in PMBG mice as it did in RBMG. On the other hand, the response to JMV3002 seen in PBMG was hallmarked by singular transcriptional response in the midbrain characterized by a simultaneous increase in both tyrosine hydroxylase ( Th ) and Proopiomelanocortin ( Pomc ) expressions. In conclusion, our data show that differences in the expression of genes related to the reward system in the midbrain as well as in ghrelin concentrations in serum correlate with spontaneous variability in body mass and food intake seen in age-matched male Swiss mice. Highlights: Age-matched Swiss mice are either prone or resistant to body weight gain. Mice prone to body weight gain display increased spontaneous food intake. Mice prone to body weight gain have increased midbrain expression of Ghsr and Drd2 . Mice resistant to body weight gain exhibit a drop in ghrelin levels after refeeding. GHSR blockade fails to inhibit food intake in mice prone to body weight gain.